PENERIMAAN CALON SISWABARU DAN PENENTUAN PENJURUSAN DENGAN ALGORITMA C 4.5 SMK PLUS PGRI 1 CIBINONG - Sumpena Sumpena; Yuma Akbar; Nirat Nirat (STIKOM CKI, 2018)
ABSTRACTEducational institutions at the moment especially Vocational Schools are required to have superior competitiveness in all sectors by utilizing all the resources they have, including prospective students - they must have the special expertise they have as long as they study at Vocational High Schools (Vocational High Schools) . Decission tree method is a flowchart structure that is similar to a tree structure, each tree point is an attribute that has been tested, each branch is a test result, and the end point is a class division produced C4.5 algorithm and decision tree are two inseparable models, because to build a decision tree, it needs a C4.5 algorithm. From the existing problems, a method is used to classify prospective students based on majors, namely by using the C.45 algorithm method and Rapid Miner Application. Keywords: Majoring in prospective students, Decission Tree, C.45 Algorithm